Attitudes and beliefs of patients with chronic depression toward antidepressants and depression - Jacob SA (Dove Medical Press, 2015)
Sabrina Anne Jacob,1 Ab Fatah Ab Rahman,2 Mohamed Azmi Ahmad Hassali3 1School of Pharmacy, Monash University Malaysia, Sunway, 2Faculty of Health Sciences, Gong Badak Campus, Universiti Sultan Zainal Abidin (UniSZA), Kuala Terengganu, 3School of Pharmaceutical Sciences, University of Science Malaysia, Minden, Malaysia Background: Many patients have erroneous views with regard to depression and its management, and it was noted that these attitudes and beliefs significantly affected their adherence rates.Objectives: The primary aim of this study was to determine the attitudes and beliefs of patients with depression toward depression and antidepressants. A secondary aim was to assess the influence of ethnicity on patients’ attitudes and beliefs.Patients and methods: The study involved patients with chronic depression being followed up at an outpatient clinic at a government-run hospital in Malaysia. Patients’ attitudes and beliefs were assessed using the Antidepressant Compliance Questionnaire.Results: A total of 104 patients of Malay, Chinese, and Indian ethnic groups met the selection criteria. Chinese patients had significantly negative attitudes and beliefs toward depression and antidepressants compared to Malays and Indians (b=-8.96, t103=-3.22; P<0.05). Component analysis revealed that 59% of patients believed that antidepressants can cause a person to have less control over their thoughts and feelings, while 67% believed that antidepressants could alter one’s personality; 60% believed it was okay to take fewer tablets on days when they felt better, while 66% believed that antidepressants helped solve their emotional problems and helped them worry less.Conclusion: Patients had an overall positive view as to the benefits of antidepressants, but the majority had incorrect views as to the acceptable dosing of antidepressants and had concerns about the safety of the medication. Assessing patients’ attitudes and beliefs, as well as the impact of their respective cultures, can be used in tailoring psychoeducation sessions accordingly. Keywords: Chinese, Malaysia, ethnicity, culture